Tumor necrosis factor-alpha: a promising therapeutic target for asthma? - Heffler, E; Berry, M; Pavord, I (2007)
Asthma is a disease that encompasses a variety of features including airway smooth muscle abnormalities, airway inflammation, and structural changes in the airway. Historically, it has been classified depending on the severity of the disease, the frequency of symptoms, and the level of treatment required to control them. Severe or refractory asthma accounts for approximately 10% of the patient population with asthma and for about 30% of the healthcare costs of this disease. It is often associated with conditions that might lead to activation of innate immunity in the lung, and it has been suggested that some of the features of severe asthma might be due to upregulation of the tumor necrosis factor-alpha (TNFalpha) pathway. In support of this, studies have shown that severe asthma is associated with an increased presence of TNFalpha within the airway and an increase in TNFalpha expression on peripheral blood mononuclear cells. Moreover, TNFalpha has the ability to induce several of the pro-inflammatory changes associated with severe asthma. Interest in the role of TNFalpha in severe asthma has increased following reports that antagonism with etanercept or infliximab is associated with improvement in asthma control in patients with severe asthma. In this article, we discuss the biology, function, and clinical effects of TNFalpha with particular reference to severe asthma.